Evidence Based Guidelines to Improve Engagement and Par- ticipation for People Experiencing Depression - Hitch , Danielle (International Journal of Psychosocial Rehabilitation, 2013)
Background Depression can have a strongly negative impact on a person’s ability to engage with and participate in activities of daily living. Clinicians currently seeking guidance on best practice in this area currently need to access and cri- tique a wide range of evidence from a number of disciplines. While some clinical practice guidelines are avail- able, this form of evidence presentation presents several barriers to implementation. Procedures This article proposes a new procedure for developing guidance for clinicians, known as evidence based guidelines. The purpose of the guidelines presented here is to provide guidance on appropriate assessment and in- tervention strategies with people experiencing depression, who wish to improve their engagement and participa- tion in daily activities. They were constructed using a multiple methods procedure, with five phases. Results Evidence based guidelines for the general population, older adults and people with co-morbid physical conditions are presented at the conclusion of this article. Conclusion The procedure described here produces evidence based guidelines with built in measures to promote implementa- tion into practice. The resulting guidelines for depression will enable clinicians from all disciplines to engage in best practice, and assist people with depression participate more fully in their lives.